Experimental investigation of the bubble separation route for an axial gas–liquid separator for TMSR. (November 2016) - Yin, Junlian; Ma, Yanfei; Qian, Yalan; Wang, Dezhong
Highlights: The two-phase flow development in an axial gas–liquid separator were discovered. The bubbles can only be totally separated under certain modes. The instability of the two-phase flow swirl evolution is related to the the axial velocity. Abstract: The gas–liquid separator plays a key role in the fission gas removal system for Thorium Molten Salt Reactor (TMSR). The separation principle in swirling flows indicates that the bubbles will be gathered in the swirl chamber center. These bubbles can be collected in three ways, including through the upstream orificeonly (UO), the downstream orifice (DO) only or two orifices simultaneously (TO). As a follow-up study, this paper is focused on the effect of the bubble collection on the separator performances. To do this, experiments for each collection scheme were conducted under different Reynolds numbers and swirling numbers. The experimental results suggest that the collection ways influence the two-phase flow patterns dramatically. To compare the performances between the TO and UO, the critical backpressure and the liquid entrainment ratio were summarized. The results show that the critical backpressure for the UO is much higher than that for the TO. However, the liquid entrainment ratio for the UO is very close to that for the TO. Therefore, the selection of the separation path is of significance to the efficient operation of the gas–liquid separator.